Apostle Paul and the earliest church : Ephesus, Antioch, Tarsus, Galatia-an illuminating visit to the place where the New Testament took place. - Bulbul, Nurettin; Konutgan, Behnan; Enis, Sakirgil; Sun, Ilteris; Wilson, Mark W. (Worcester, Pa : Gateway Films/ Vision Video, 2004)
Recounts the missionary journeys of the Apostle Paul in the Anatolian region, the area known today as Turkey. Presents dramatic reenactments depicting Paul's miracles, persecution, and other key events. The archaeological emphasis is enhanced by 3D animated maps and footage of Antioch on the Orontes, Pisidian Antioch, Ephesus, Tarsus and other cities important to Paul's ministry.
" Paul the emissary: from the pages of the New Testament, the world-changing saga of the Apsotle Paul"-- cover
English, Turkish, and Arabic language tracks.
Not rated
2 in 1
Contents: Paul's calling-- First missionary journey --Second missionary journey --Third missionary journey -- A lasting legacy
Keywords: Paul, The Apostle, Saint -- Travel -- Turkey; Christian Saints -- Turkey -- Tarsus -- Biography; Bible.N.T. -- Antiquities